The Relationship Between Intercultural Sensitivity and Speaking Skills: Voices in Higher Education - Fitriani Fitriani; Dwiyani Pratiwi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aimed to assess the levels of intercultural sensitivity among students and to explore the potential correlation between intercultural sensitivity and the speaking proficiency of English department students in Indonesian institutions. To achieve these goals, a descriptive study design utilizing both quantitative and qualitative methods was employed. Data collection involved a questionnaire and interviews, with 64 students participating as respondents. The questionnaire included 24 items from the Intercultural Sensitivity Scale (ISS), which were answered on a four-point Likert scale. The questionnaire was distributed via Google Forms. To assess speaking ability, the researcher conducted interviews focused on language and cultural descriptions, which were evaluated using a custom rubric. The findings revealed that students exhibited high levels of intercultural sensitivity in terms of intercultural attentiveness, confidence, and engagement. Additionally, they showed moderate sensitivity in interaction enjoyment and respect for cultural differences. Statistical analysis indicated a correlation between intercultural sensitivity scores and students' perceived speaking proficiency. Future research could explore different aspects of intercultural sensitivity to observe students' practical behavior in cross-cultural interactions.